2017
DOI: 10.1159/000462981
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Use of Biotin for Hair Loss

Abstract: Background: Biotin has gained commercial popularity for its claimed benefits on healthy hair and nail growth. Despite its reputation, there is limited research to support the utility of biotin in healthy individuals. Objective: To systematically review the literature on biotin efficacy in hair and nail growth. Methods: We conducted a PubMed search of all case reports and randomized clinical trials (RCTs) using the following terms: (biotin and hair); (biotin and supplementation and hair); (biotin supplementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
66
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 26 publications
(25 reference statements)
1
66
0
7
Order By: Relevance
“…At the same time, potential additional causes of hair loss, such as androgenetic alopecia, other nutritional deficiencies, and endocrine disorders, must be systematically addressed and treated as well." I totally agree with Patel et al [1] that the custom of treating hair loss in an indiscriminate manner with oral biotin supplementation is to be rejected, and that there is a need for randomized controlled studies to validate the additional benefit of biotin supplementation in individuals with hair loss of multifactorial origin with biotin deficiency or marginal biotin levels.…”
supporting
confidence: 53%
See 3 more Smart Citations
“…At the same time, potential additional causes of hair loss, such as androgenetic alopecia, other nutritional deficiencies, and endocrine disorders, must be systematically addressed and treated as well." I totally agree with Patel et al [1] that the custom of treating hair loss in an indiscriminate manner with oral biotin supplementation is to be rejected, and that there is a need for randomized controlled studies to validate the additional benefit of biotin supplementation in individuals with hair loss of multifactorial origin with biotin deficiency or marginal biotin levels.…”
supporting
confidence: 53%
“…Dear Editor, I read with interest "A review of the use of biotin for hair loss" by Patel et al [1]. The authors are to be commended for their intention to clarify whether there is medical evidence for the current practice of treating hair loss in otherwise healthy individuals with oral biotin.…”
Section: Ludwig Wittgenstein (1889-1951)mentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, isotretinoin-associated TE and alopecia secondary to valproic acid may benefit from biotin supplementation [76,77]. A recent review identified 11 cases of hair loss secondary to biotin deficiency, from either an inherited enzyme deficiency or medication, where biotin was an effective supplementation for hair regrowth [78]. Current clinical evidence supports biotin supplementation as an effective CAM for hair loss only in cases secondary to biotin deficiency; however, apart from medications, this is rare in developed countries due to well-balanced dietary intake [79].…”
Section: Vitamin B 7 (Biotin)mentioning
confidence: 99%